Kajian Pembuatan Akta Otentik oleh Notaris Selama Pandemi Covid-19 di Indonesia - Vera Evantiana Sukma Wardani; Aisyah Ayu Musyafah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In particular, the call to work from home and implement social distancing. The implementation of WFH is not a formal violation of Article 17 of Law 30/2004 concerning the Office of a Notary. Some of the implementation of the duties of a notary in making a deed by changing the schedule for shooting documents with appearers until circumstances allow, recommending other notaries who allow them to carry out their duties and agreements, deeds, or meetings which according to the laws and regulations the documents can be made privately, to include the clause "will be made/restated in the Authentic Deed as soon as the Covid-19 emergency is revoked by the Government.